Efficacy of vanillin and geraniol in reducing Escherichia coli O157:H7 on strawberry juice. Issue 2 (December 2015) - Tomadoni, B.; Cassani, L.; Moreira, M.R.; Ponce, A.
Abstract In the present study, vanillin (Van) and geraniol (Ger) were studied as potential food biopreservatives. Minimal Inhibitory Concentration (MIC) was obtained in vitro using four different pathogens as indicators. Studies in vivo in strawberry juice inoculated with Escherichia coli O157:H7 were conducted to evaluate the pathogen survival. Biopreservatives were applied at 1 and 2 MIC concentration. Samples were stored at 5 °C during 14 days, in order to study the effects of the treatments against the inoculated pathogen. At day 0, untreated sample showed counts of 5.4 log CFU/mL. Samples treated with Van2MIC, Ger1MIC, Ger2MIC showed a significant control on E. coli population at day 0 (immediately before application of the compounds), with counts of 3.0–3.2 log. Furthermore, from day 3 until the end of storage, those samples showed E. coli counts below the detection limit. More studies should be made in order to investigate the impact of vanillin and geraniol application on sensory and nutritional characteristics of strawberry juice, and the effects on its native microflora and spoilage microorganisms.